2022
DOI: 10.1097/tp.0000000000004215
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Released During Normothermic Machine Perfusion Are Associated With Human Donor Kidney Characteristics

Abstract: Background. Extracellular vesicles (EVs) are tissue-specific particles released by cells containing valuable diagnostic information in the form of various biomolecules. The characterization of EVs released by kidney grafts during normothermic machine perfusion (NMP) may present a promising avenue to assess graft status before transplantation. Methods. We phenotyped and determined the concentrations of EVs in the perfusate of 8 discarded expanded-criteria donor human kidneys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…For example, mass spectrometry was used in one recent study to show that NMP with urine recirculation preserves and revitalizes kidney metabolism, primarily by reducing the abundance of damage-associated molecular patterns (DAMPs), improving mitochondrial glucose metabolism, and minimizing biochemical alterations induced by I/R injury 9 . Furthermore, nanoparticle tracking analysis demonstrated that discarded ECD kidney grafts release distinct extracellular vesicles (EVs) during NMP that may be suitable for the assessment of kidney graft quality 10 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, mass spectrometry was used in one recent study to show that NMP with urine recirculation preserves and revitalizes kidney metabolism, primarily by reducing the abundance of damage-associated molecular patterns (DAMPs), improving mitochondrial glucose metabolism, and minimizing biochemical alterations induced by I/R injury 9 . Furthermore, nanoparticle tracking analysis demonstrated that discarded ECD kidney grafts release distinct extracellular vesicles (EVs) during NMP that may be suitable for the assessment of kidney graft quality 10 .…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that EVs not only hold the potential to deliver therapeutics but also serve as pretransplant biomarkers. 56 …”
Section: Gene Delivery Methodsmentioning
confidence: 99%
“…This conjugation can both simplify and enhance the use of nanomaterials to target graft endothelial cells, opening opportunities to deliver therapeutics with efficacy prior to transplant. Woud 10 and the team from Rotterdam, Netherlands, analyzed the excretion of small Extracellular Vesicles (EV) during normothermic machine perfusion of kidneys as a potential biomarker both before and after transplantation. Eight discarded human kidneys were perfused in a closed system at 37°C for 6 h. Perfusate samples were taken before and at 1, 3, 6 h. They observed a positive correlation of EV levels with donor age and kidney weight, while negative correlations were found for ischemia time.…”
Section: Kidney Novel Techniques and Methodsmentioning
confidence: 99%